Noise performance of textile‐based dry ECG recording electrodes - Maji, Soumyajyoti; Burke, Martin J. (Electronics letters, 2021)
This study reports attempts to characterise the noise properties of un‐gelled, textile‐based electrodes intended for use in ECG recording in wearable garments. Measurements were made using very low noise operational amplifiers and with mains power supply interference eliminated from the recorded signals so that they reflected only genuine noise. Measurements were carried out on four conductive fabric electrodes, one conductive rubber electrode and a standard self‐adhesive, gelled electrode on three male and three female subjects. Curves of the form y = K/f + C were fitted to the recorded noise spectral density functions. Coefficients obtained for the white noise spectral density ranged from 1.1 to 5.6 nV/√Hz and for the flicker (1/f) noise spectral density ranged from 8 to 80 nV√Hz.